Analisis Pemanfaatan Media Sosial Sebagai Strategi Pemasaran Dalam Meningkatkan Daya Saing Produk Agribisnis - Alisya Adelia; Dafin Hartono; Lokot Muda Harahap; Erwin Nardo Sinaga; Silvia Lamriang Pardede; Sonya Lalla Saragih (AMMA : Jurnal Pengabdian Masyarakat, 2026)
This study aims to analyze the utilization of social media as a marketing strategy in enhancing the competitiveness of agribusiness products. The research employs a qualitative descriptive approach using a literature review method, with secondary data obtained from scientific journals, books, official reports, and credible publications. The results indicate that social media plays a significant role in agribusiness marketing, not only as a promotional tool but also as a medium for communication, information distribution, and brand building. The use of social media has been proven to increase market reach, sales volume, product differentiation, cost efficiency, and consumer trust. However, several challenges remain, including limited digital literacy, uneven internet access, and lack of consistency in social media management. Therefore, optimization strategies such as creating engaging content, maintaining consistency, and maximizing digital features are essential. Overall, social media serves as a strategic instrument in driving digital transformation and enhancing the competitiveness of the agribusiness sector in the modern era.